Study of heat and mass transfer on MHD Walters B′ nanofluid flow induced by a stretching porous surface - S.R. Mishra; S. Baag; M.M. Bhatti (Alexandria Engineering Journal, 2018)
This communication deals with the role of heat and mass transfer in a Walters B′ (non-Newtonian) nanofluid fluid flow through a stretching vertical porous surface. The behavior of Brownian motion, chemical reaction, thermophoresis and heat generation/absorption are also taken into consideration. A suitable similarity transformation variable is utilized to model the equations of nanoparticle concentration, momentum, and thermal energy. These ordinary differential equations are solved analytically by means of perturbation technique and then solved numerically using fourth-fifth order Runge–Kutta method. The behavior of all the sundry parameters are discussed and demonstrated via graphs. Furthermore, Sherwood number, Nusselt number and skin friction coefficient are also displayed via graphs. A numerical comparison is also presented against skin friction coefficient, Nusselt number and Sherwood number with previously published data. Keywords: Non-Newtonian nanofluid, Vertical stretching surface, Heat source/sink, Chemical reaction, Magnetic field